G162 Evidence that an immersive virtual reality scenario can be used to train safeguarding to doctors in primary care. (12th March 2018) - Fertleman, CR; Pan, X; Delacroix, S
Abstract : Introduction: Most child protection will be seen in primary care but is often subtle. Methods: We invited GPs to undertake a medical consultation in a virtual reality 'cave'. We obtained ethical approval from UCL for this being a covert child safeguarding scenario: participants were informed that they were testing the use of Virtual Reality in GP consultation. We produced a simulated consultation using two avatars: Chris, who came for a medically challenging consultation, and his accompanying 6 year old son Tom. Safeguarding cues presented were either subtle or obvious. Chris was angry towards his son, refused to allow Tom to go to the toilet and appeared to swipe at him. Results: We recruited 63 GPs (26 male; 33 female) who ranged in age from 25 to 59 years and had worked between 1 and 36 years. Fourteen GPs failed to detect the safeguarding cues (3 in the obvious cue scenario and 13 in the subtle cue scenario). Analysis of the post scenario questionnaire provides useful information about the use of virtual reality in medical training. One important question posed after the scenario was 'Were you concerned about Tom's relationship with Chris?' This clearly cued those who hadn't picked up on this previously. All participants including these 14 GPs made comments that they had some concerns about what was going on (see Table). One participant's comments sum it up well. 'He swiped at him at the beginning of the consultation, made a disparaging comment and did not let him go to the toilet'. Discussion: The GPs responses to this virtual reality scenario were very interesting. Most of their comments can be applied to real life scenarios but this has to take advantages over using role play often considered as the 'gold-standard'. Young children cannot be used as actors as they are unable to divorce play from reality. This becomes even more pertinent if the subject matter is child protection where there is something unpalatable about using young children who are being abused. By directly filling the questionnaires after undertaking the scenario those who had missed that this was a safeguarding scenario could be cued in a way to reconsider what had happened in a private and constructive way.